COVID-19 Pandemic: An Islamic Analysis - Chowdury, Saeyd Rashed Hasan; Alam, Prof. Dr. Md. Shamsul; Numani, Prof. Dr. Abu Jamal Md. Qutubul Islam; Göktaş, Prof. Dr. Vahit (CenRaPS Journal of Social Sciences, 2021)
The study's purpose is to analyse the prevention of the Covid-19 Pandemic in the light of the Holy-Qur'an and Prophet Muhammad (Pbuh)’s Sunnah. Just as a Pandemic, disaster, or calamity in the world has some external causes, it also has some internal and subtle reasons. Islam considers the plague as a punishment in a natural and broad sense; simultaneously, Islam believes this epidemic to be a test and a warning for the believer. Besides, Islam thinks that dangers and calamities happen according to Almighty Allah's judgment. Islam always gives the idea of a healthy-capable human group. There are 'Kitabut Tib' or medical chapters in almost all Hadith texts regarding the importance of health and treatment. The golden branch of Islam was the development of a particular scripture called the Prophet in Tibet. If there is a Pandemic in a specific area, Islam prescribes quarantine and lockdown. Modern medical systems embraced this warning fourteen hundred years ago as the only way out. In this context, Muhammad (pbuh) said people would not enter the area affected by the pandemic. Besides, people will not go out of where the epidemic has spread [1]. The damage caused by the outbreak could have been drastically reduced if the hadith teachings had been implemented at this critical time in the Coronavirus's presence. To survive the Coronavirus, the World Health Organization (WHO) always says to stay clean. Islamic law orders a Muslim who believes that he is immaculate at every stage of his life. The Prophet Muhammad (pbuh) said: Cleanliness is a part of faith [2]. There are various dispositions of the Shari'a that have been prescribed as a means of attaining holiness. According to medical science's advice, Islam advises taking treatment and taking precautionary measures in a Pandemic of any disease.